Safety and reliability in the oil and gas industry : a practical approach - Dhillon, B. S. 1947- (Safety first, 2016)
"Designing, constructing, operating, and maintaining offshore oil and gas industry equipment and systems can sometimes result in accidents, injuries, and other serious problems. Safety and Reliability in the Oil and Gas Industry: A Practical Approach focuses on oil and gas industry equipment reliability, offers useful and up-to-date information on the subject, and covers in a single volume the most common safety and reliability engineering issues in the oil and gas industry. The book introduces the latest developments in the area, and provides relevant methods and approaches. It also presents important aspects of various case studies on major accidents in the oil and gas industry, and considers human factors that contribute to accidents and fatalities in the area of oil and gas. Additionally, this book describes: -Mathematical concepts -Oil and gas industry equipment reliability characteristics -Accident data and analysis -Mathematical models used for performing safety and reliability-related analyses in the industry Safety and Reliability in the Oil and Gas Industry: A Practical Approach covers important aspects of safety in the offshore oil and gas industry. A reference designed with engineering professionals in mind, this book can also be used in oil- and gas-industry-related courses, and serves as a guide for anyone concerned with safety and reliability in the area of oil and gas."--